KEHADIRAN NEGARA DALAM PENGELOLAAN SUMBER DAYA AIR DI PERBATASAN NEGARA REPUBLIK INDONESIA – REPUBLIK DEMOKRATIK TIMOR LESTE (RI-RDTL) - Antik Tri Susanti (Universitas Kristen Satya Wacana, 2014)
The majority (76%) boundary between the Republic of Indonesia and the Democratic Republic of Timor-Leste (RDTL) is a river. There are rivers upstream and or hilirnya are in the two countries. Water resources will thus be utilized by the two countries. In such situations it is necessary the presence of the State to guarantee the fulfillment of the water in the border region SO. Therefore this research was conducted to determine the presence of the State in the management of water resources in the border region in the 5 aspects: aspects of the conservation of water resources, efficient use of water resources, water damage, power control of information system of water resources (SISDA) and community empowerment. Exploratory qualitative research, carried out in the region of the River (WS) Noelmina in DAS Naekake in the village of Tasinifu, village of Naekake A, in district of North Central Timor Regency Mutis, river basin (WS) Benenain on DAS Alas in the village South-East of Kobalima Sub-district Pedestal District of Malacca, DAS Sarabau Village in Kecamatan Talao Tasifeto Timur Regency of Belu and the village of Asumanu district of Belu, Raihat and DAS Maumutin Raihat Belu District. The results of this research indicate the presence of the State is still very minimal/weak in management of the SDAS in the border region SO-RDTL.Keywords: State presence, water resources, water-damaged power facilities, water resource information system, community empowerment, the border region SO-RDTL.